2008
DOI: 10.1007/s10865-008-9169-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of race-, sexual orientation-, and HIV-related discrimination with adherence to HIV treatment: a pilot study

Abstract: Adherence to highly active antiretroviral therapy (HAART) must be close to perfect in order to maintain suppression of HIV viral load, and to prevent the development of drug resistant strains of HIV. People living with HIV (PLWH) often report low levels of adherence. One variable that has been linked to poor adherence is perceived discrimination; however, research has generally not considered the possible unique effects of different types of discrimination on adherence. The present pilot study aimed to examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 50 publications
2
23
0
1
Order By: Relevance
“…Consistent with prior research supporting an association between discrimination and adherence [17, 18, 28, 29], a greater number of discrimination experiences were associated with worse treatment adherence over 6 months.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Consistent with prior research supporting an association between discrimination and adherence [17, 18, 28, 29], a greater number of discrimination experiences were associated with worse treatment adherence over 6 months.…”
Section: Discussionsupporting
confidence: 85%
“…However, only a few small studies have examined the effects of the layering of stigma from multiple devalued social categories. In a study of 57 people with HIV (47% Black), perceived racism was the only significant correlate of self-reported antiretroviral treatment nonadherence in multivariate analyses controlling for discrimination due to HIV-serostatus and sexual orientation [28]. A study of 101 people with HIV (45% Black) found that perceived discrimination in health care due to social class was significantly associated with self-reported antiretroviral treatment nonadherence and missed medical appointments, whereas perceived discrimination due to race/ethnicity was not significantly related to either HIV care measure [29].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] Amongst certain minorities, there is a history of discrimination that continues to inform current perceptions about health care and can lead to distrust in treatments espoused by the health care system. 34 Interestingly, in our subgroup analysis, we found that perceived discrimination was a barrier to medication adherence in Hispanics, but not in African Americans.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the ART adherence measure, which is a clinically valid measure utilized in a variety of settings, lacks specificity, which can result in an overestimation of adherence rates. [26][27][28][29][30] Furthermore, information on specific illicit drugs used by participants was not collected. Therefore, we were unable to assess differences between specific agents and ART adherence.…”
Section: King Et Almentioning
confidence: 99%